Perbaikan Struktur Bangunan Pasca Gempa dengan menggunakan Serat Karbon (Studi Kasus Gedung Kantor Bea dan Cukai Teluk Bayur Padang) - Elvi Roza Syofyan (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2016)
In the last ten years, the area west coast of Sumatra island has several times experienced the earthquake with strong intensity. Starting from the earthquake in Aceh December 26, 2004 until 30 September 2009 earthquake Pariaman ago. The last earthquake measuring 7.9 on the Richter scale has killed more than 1,000 people and damaged buildings 279 432, with 50 percent of them were severely damaged. Another alternative that is better than doing demolition is to retrofit. In general, the retrofit can be described as the addition of new technology or new technology on a merger between the old system (which already exists). In other words, the retrofit is the process of retrofitting old buildings with the aim of making these buildings resistant to earthquakes. From the calculation and analysis conducted on the carbon material, the material Sika Wrap Hex 230C can be used to retrofit House Office Building Customs Bayur Gulf of Padang. The method of implementation should be properly cared for, so that the strength of the building is expected back as they are resistant to earthquakes. It should be noted once in choosing the method of retrofitting that we will use.